Longitudinal Average Attributable Fraction as a Method for Studying Time-Varying Conditions and Treatments on Recurrent Self-rated Health: The Case of Medications in Older Adults with Multiple Chronic Conditions - Allore, Heather G. (Ann Epidemiol, 2015)
PURPOSE: The objective is to modify the longitudinal extension of the average attributable fraction (LE-AAF) for recurrent outcomes with time-varying exposures and control for covariates. METHODS: We included Medicare Current Beneficiary Survey participants with two or more chronic conditions enrolled from 2005-2009 with follow-up through 2011. Nine time-varying medications indicated for nine time-varying common chronic conditions and 14 out of 18 forward-selected participant characteristics were used as control variables in the generalized estimating equations step of the LE-AAF to estimate associations with the recurrent universal health outcome self-rated health (SRH). Modifications of the LE-AAF were made to accommodate these indicated medication-condition interactions and covariates. Variability was empirically estimated by bias-corrected and accelerated bootstrapping. RESULTS: In the adjusted LE-AAF, thiazide, warfarin and clopidogrel had significant contributions of 1.2%, 0.4%, 0.2% respectively to low (poor or fair) SRH; while there were no significant contributions of the other medications to SRH. Hyperlipidemia significantly contributed 4.6% to high SRH. All the other conditions except atrial fibrillation contributed significantly to low SRH. CONCLUSIONS: Our modifications to the LE-AAF method apply to a recurrent binary outcome with time-varying factors accounting for covariates.